2-adic morphogenesis as a metaphorical model of biological growth. (February 2022) - Ignatov, Victor V.
Abstract: The article proposes a mathematical model of morphogenesis which is based on 2-adic arithmetic. In this model, the process of morphogenesis is separated from its genetic coding and genetic control, and is considered abstractly as a transformation of complex biomorphic structures resulting from the process of sequential geometric cell division. The concept of cellular structure is introduced and the analogies that exist between the transformation of organisms and the transformation of the corresponding cellular structures generated by numerical series are considered, in particular, an analogy is drawn between the transformation of series depending on a complex parameter and the growth of biological organisms. The article also introduces some mathematical formalism used to compare different morphological pathways.